Service user perspectives and experiences of their diagnosis of psychotic major depression: A qualitative study - Emilia May Loane; Norha Vera San Juan; Allan H. Young; Oliver Gale-Grant; Margaret Heslin (PLoS ONE, 2025)
Background Evidence suggests psychotic major depression can be overlooked in clinical settings and thus lead to delays in diagnosis. There have been multiple theories about why this happens, however no research has investigated this from a service users’ perspective. Aims The aim of this study was to explore service users’ perspectives and experiences of their diagnosis of psychotic major depression. Where there appeared to be a substantial delay between initial symptoms and diagnosis, reasons for this was explored in depth. Methods This study used a qualitative approach based on semi-structured interviews with service users diagnosed with psychotic major depression. Interviews were audio recorded and transcribed verbatim. Data was analysed using thematic analysis. Results Ten interviews were conducted. Four overarching themes were identified: difficulty retelling the story, barriers to symptom identification, experiences following disclosure, responses to diagnosis. The theme of barriers to symptom identification highlighted that psychotic symptoms can be overlooked in the diagnostic process. Service users reported that health professionals do not always check for psychotic symptoms in clinical assessments. Service users have difficulty verbalising their symptoms, or find it difficult to disclose due to stigma, fear or shame. Short/rushed appointments, lack of consistency with health professionals, being moved between services and medicalising language made disclosure of psychotic symptoms less likely. Conclusions Psychotic major depression should be actively considered as a differential diagnosis by healthcare professionals when assessing an individual for unipolar depression. Healthcare professionals should be mindful of the specific barriers to disclosure of psychotic symptoms, and building rapport should be prioritised to facilitate disclosure.